Writing for Inquiry and Research - Kessler, Jeffrey; Bennett, Mark; Primeau, Sarah; Williams, Charitianne; Costello, Virginia; Armstrong, Annie R. (Open textbook library., 2023)
Writing for Inquiry and Research guides students through the composition process of writing a research paper. The book divides this process into four chapters that each focus on a genre connected to research writing: the annotated bibliography, proposal, literature review, and research essay. Each chapter provides significant guidance with reading, writing, and research strategies, along with significant examples and links to external resources. This book serves to help students and instructors with a writing-project-based approach, transforming the research process into an accessible series of smaller, more attainable steps for a semester-long course in research writing. Additional resources throughout the book, as well as in three appendices, allow for students and instructors to explore the many facets of the writing process together.